UNDERLYING FACTORS OF ATTITUDE AND INTENTION TOWARDS KNOWLEDGE SHARING AMONG EMPLOYEES: THE CASE OF THE HOTEL BUSINESS IN AMBON, INDONESIA - Join Rachel Luturmas; Nurul Indarti (Faculty of Economics and Business, Universitas Gadjah Mada, 2016)
Studies into knowledge sharings’ attitudes and intentions, in the context of the hotel industry, have received relatively little attention. This current study is intended to fill that void and contribute to the existing discussion of knowledge sharing studies of hotel businesses. The main objective of the current study is to examine: 1) the effect of extrinsic motivation, absorptive capacity, channel richness and sense of self-worth on people’s attitude towards knowledge sharing, and 2) the effect of people’s attitudes towards knowledge sharing and the intention to share knowledge. The study mainly uses the Theory of Reasoned Action (TRA) as the point of departure to understand the attitude and intention of knowledge sharing. It also proposes six hypotheses. We conducted a survey among 300 employees from various hotels in the city of Ambon, Indonesia. The data are tested using Structural Equation Modelling (SEM) techniques. The findings substantiate theoretical discussions and previous studies. The extrinsic motivation, absorptive capacity, and in-role behaviour have a positive effect on the attitude towards sharing knowledge. In addition, the attitude to knowledge sharing has a positive influence on the intention to share knowledge. Meanwhile, the effect of channel richness and the sense of self-worth on the attitude to knowledge sharing are not supported. The study also provides suggestions for hotel businesses to offer extrinsic rewards and improve their employees’ skills in order to enhance the employees’ absorptive capacities.